1993
DOI: 10.1139/y93-109
|View full text |Cite
|
Sign up to set email alerts
|

Partners in defense, vitamin E and vitamin C

Abstract: In addition to the enzymic mechanism of free-radical removal, essential nutrients that can scavenge free radicals, such as vitamins E and C, constitute a strong line of defense in retarding free radical induced cellular damage. Distinct pathways for the repair of oxidized vitamin E in human cells have been recently identified. Within 0.5 min after the addition of arachidonic acid to a human platelet homogenate, over half of the platelet vitamin E and added arachidonate were metabolized by platelet cyclooxygena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
187
0
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(202 citation statements)
references
References 0 publications
6
187
0
9
Order By: Relevance
“…4 Additionally, ascorbate can regenerate ␣-tocopherol (the most active form of vitamin E) from the tocopherol radical, thus decreasing the vitamin E radical by means of a recycling mechanism. [36][37][38] Other areas of ongoing research have investigated the anti-inflammatory and wound-healing effects of ascorbic acid as well as its photopreventive effects against cutaneous malignancy. Very little information is available on the topographic changes in photodamaged facial skin associated with topical ascorbic acid application.…”
Section: Commentmentioning
confidence: 99%
“…4 Additionally, ascorbate can regenerate ␣-tocopherol (the most active form of vitamin E) from the tocopherol radical, thus decreasing the vitamin E radical by means of a recycling mechanism. [36][37][38] Other areas of ongoing research have investigated the anti-inflammatory and wound-healing effects of ascorbic acid as well as its photopreventive effects against cutaneous malignancy. Very little information is available on the topographic changes in photodamaged facial skin associated with topical ascorbic acid application.…”
Section: Commentmentioning
confidence: 99%
“…Indeed, some studies of Chagas disease 39,40 have shown that one of the host mechanisms in the acute phase of infection involves upregulation of the antioxidant defense system through GSH. This finding suggests that GSH production might constitute a major defense mechanism against oxidative stress in the acute phase of the disease, which would act to maintain the sulfhydryl groups of proteins, eliminate peroxides, and regenerate antioxidant vitamins such as vitamins C and E.…”
Section: Discussionmentioning
confidence: 99%
“…Since dietary vitamin C intake was similar in all subjects, the low plasma ascorbate concentrations in smokers probably re¯ects an increased ascorbate turnover (Brown et al, 1997). Kinetic studies demonstrate an intracellular interaction between vitamin C and vitamin E whereby the membrane-bound oxidized vitamin E is regenerated nonenzymically by ascorbate at the membrane cytosol interface (Chan, 1993).…”
Section: Discussionmentioning
confidence: 99%